Bosnia and Herzegovina : Accounting and Auditing Technical Note - World Bank (World Bank, Washington, DC, 2015)
This Technical Note was prepared in the context of a joint World Bank-IMF Financial Sector Assessment Program mission in Bosnia and Herzegovina during October-November 2014. Bosnia and Herzegovina has substantially aligned its accounting and auditing laws with the EU acquis communautaire and will need to implement the new Directives on Accounting and Auditing in 2016.